Closed-form solutions for analysis of cylindrically conformal microstrip antennas with arbitrary radii - He, Mang; Xu, Xiaowen (IEEE transactions on antennas and propagation, 2005)
An efficient and accurate closed-form solution, based on the spectral-domain method of moments (MoM), is presented to analyze the characteristics of cylindrically conformal microstrip antennas with arbitrary radii. First, an algorithm that combines the recursive and the uniform asymptotic expansion method in different regions is developed to calculate the spectral-domain Green's functions for arbitrary dielectric coated cylinders accurately. Next, the integrands of the spectral integrals involved in MoM equation are partitioned into two parts, i.e., the fast oscillatory, slowly convergent part and the well-behaved part. Consequently, all of the integrals in MoM analysis can be categorized into two types. Through the Sommerfeld identity and its extension, these integrals are cast into closed-forms by using the nonlinear approximation method (generalized pencil-of-function method). In this method, any time-consuming numerical integration procedure is eliminated, which improves the computational efficiency drastically. Compared with the results from published references, the validity and accuracy of the method are demonstrated.